1994
DOI: 10.1002/mrc.1260320805
|View full text |Cite
|
Sign up to set email alerts
|

Proton assignment and structural features of a peptide from the chymosin‐sensitive region of bovine k‐casein determined by 2D‐NMR spectroscopy

Abstract: The peptide ~-casein(98-111) corresponding to the sequence 98-1 11 of bovine Kcasein (His-Pro-His-Pro-His-LeuSer-Phe-Met-Ala-Ile-Pro-Pro-Lys), which includes the aspartic protease sensitive region, was analysed by 2D 'H NMR spectrascopic techniques in DMSO-d, . The spectral peaks of all protons resolved at 400 MHz were assigw ed. The changes in the amide proton shifts with pH and temperature and the existence of particular crow peaks in the ROESY spectra were consistent with the central region of the peptide b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…6). However, the study by Plowman et al (1994) showed that the bond between / / i s l a n d the highly conserved (Fig. 10) Pro 99 is predominantly in the trans conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). However, the study by Plowman et al (1994) showed that the bond between / / i s l a n d the highly conserved (Fig. 10) Pro 99 is predominantly in the trans conformation.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a larger study, Plowman et al (1994) determined the likely structure of the peptide His 98 -Lys ni in d 6 -dimethylsulphoxide by two dimensional NMR spectroscopy. The resultant spectra and spectral shifts with pH and temperature were consistent with the sequence Ser 104 -A la 10? being in an extended structure with more constrained conformations for the His 98 -Leu 103 and Ile 108 -Lys ul sequences, with the His 98 -Pro", His 100 -Pro 101 , Ile W8 -Pro 109 and Pro 109 -Pro U0 bonds being in the trans conformation.…”
mentioning
confidence: 99%
“…The crystal structure of a chymosin‐inhibitor complex (RCSB PDB ID: 1CZI) and previous molecular modeling studies, suggest that κ‐casein binds to chymosin in an extended secondary structure . This is supported by circular dichroism, solution NMR and molecular modeling studies of unbound κ‐casein, all showing an extended structure in the region of the scissile bond . Molecular modeling and mutagenesis studies, propose that the P8‐P7′ residues are located in the chymosin binding cleft during catalysis.…”
Section: Introductionmentioning
confidence: 78%
“…This refers to the phosphorylated regions of the molecule of multi-phosphorylated motif Ser(P)-Ser(P)-Ser(P)-Glu-Glu, which has been shown to be critical for the interaction with amorphous calcium phosphate [74]. The peptide sequence with the Ser(P) residues that are of great importance in stabilization of casein phosphate complexes are the following [29]: These sequences have been studied extensively using the NMR for secondary structure identification, binding preferences for cations (Ca 2+ ) and aggregation preferences [25][26][27][28][29][30][31][32][33]75,76]. Most of the studies were focused on amino acids sequence analysis of αs 1 -CN and β-CN, as the predominant caseins in milk and are thus important building blocks of the casein micelle.…”
Section: Caseinsmentioning
confidence: 99%
“…Several studies that include the elucidation of the structure of peptides from the κ-CN molecule using NMR methods have been reported in the literature. Plowman et al [33] presented complete chemical assignment of the peptide κ-CN f(98-111) in an attempt to predict the secondary structure. In this study, 20 mM of the peptide was suspended in DMSO-d 6 and studied at pH 3.0 and 7.5 and temperatures in the range 22-58 • C. The NMR methods used were DQF-COSY, TOCSY and ROESY performed in the phase-sensitive mode with the TPPI method, as described by Marion et al [85].…”
Section: κ-Caseinmentioning
confidence: 99%